Induction of lipid metabolism dysfunction, oxidative stress and inflammation response by tris(1-chloro-2-propyl)phosphate in larval/adult zebrafish. (February 2022) - Yan, Jin; Zhao, Zijia; Xia, Min; Chen, Shuya; Wan, Xiancheng; He, Anfei; Daniel Sheng, Guangyao; Wang, Xuedong; Qian, Qiuhui; Wang, Huili
Graphical abstract: Highlight: Acute and chronic TCPP exposure caused excess lipid accumulation in zebrafish. TCPP exposure promoted adipogenesis and suppressed fatty acids β-oxidation. Lipid accumulation caused by TCPP triggered oxidative stress and dysimmunity. Integrating analysis from RNA-seq and CEPIA indicated the HCC risk by TCPP exposure. The HCC risk by TCPP was confirmed by overexpressed marker protein of liver cancer. Abstract: As an important organophosphate flame retardant, tris(1-chloro-2-propyl)phosphate (TCPP) is ubiquitous in the environment leading to inevitable human exposure. However, there is a paucity of information regarding its acute/chronic effects on obesity, lipid homeostasis, and hepatocellular carcinoma, especially regarding the underlying molecular mechanisms in humans. Herein, we investigated the effects of TCPP exposure (5–25 mg/L) on lipid homeostasis in larval and adult zebrafish ( Danio rerio ). TCPP exposure caused remarkable lipid-metabolism dysfunction, which was reflected in obesity and excessive lipid accumulation in zebrafish liver. Mechanistically, TCPP induced the over-expression of adipogenesis genes and suppressed the expression of fatty-acid β-oxidation genes. Consequently, excess lipid synthesis and deficient expenditure triggered oxidative damage and an inflammation response by disrupting the antioxidant system and over-expressing proinflammatory cytokine. Based on high-throughput transcriptome sequencing, we found that TCPP exposure led to enrichment of several pathways involved in lipid metabolism and inflammation, as well as several genes related to pathways of cancer. Notably, increasing expressions of Ki-67 and 53BP1 proteins, which are reliable biomarkers for recognition and risk prediction of cellular proliferation in cancer cells, were observed in liver tissues of adult zebrafish. These results imply that chronic TCPP exposure triggers a potential risk of hepatocellular carcinogenesis (HCC) progression. Collectively, these findings offer new insights into our mechanistic understanding for the health effects of organophosphorus flame retardants on humans.